Childcare markets in an age of austerity - Lloyd, Eva; Penn, Helen (European early childhood education research journal, 2014)
Public support provided for European early childhood education and care (ECEC) systems varies considerably. European ECEC systems tend to form part of a mixed economy, in which the state, private-for-profit and private-not-for-profit providers all play a role in ECEC's provision, funding and regulation, representing a market model. ECEC privatisation and marketisation in the UK has gone further than in other EU member states and there is growing evidence that these developments, including corporatisation, risk deepening, consolidating or widening inequalities of access to quality early childhood provision. The Norwegian and French systems illustrate how direct public funding and stringent regulation may counter childcare markets' potentially negative impacts. As economic austerity makes its mark on Europe, childcare market challenges are growing and the need to rethink the appropriateness of delivering UK ECEC under market conditions becomes more acute.